How not to delimit taxa: a critique on a recently proposed “pragmatic classification” of jumping spiders (Arthropoda: Arachnida: Araneae: Salticidae) - Kropf, Christian; Blick, Theo; Brescovit, Antonio D.; Chatzaki, Maria; Dupérré, Nadine; Gloor, Daniel; Haddad, Charles R.; Harvey, Mark S.; Jäger, Peter; Marusik, Yuri M.; Ono, Hirotsugu; Rheims, Cristina A.; et al. (Zootaxa, 2019)
Modern taxonomy and systematics profit from an invaluable tool that has been developed in the course of more than a century by intense discussions and negotiations of generations of zoologists and palaeontologists: The International Code of Zoological Nomenclature (ICZN 1999, 2012). The main goal of the Code is “to promote stability and universality in the scientific names of animals and to ensure that the name of each taxon is unique and distinct” (Melville 1995, ICZN 1999: 2). The provisions of the Code are generally accepted and thoroughly applied by the scientific community. Exceptions, such as the one described below, are very rare.